Anti-arboviral activity and chemical characterization of hispidulin and ethanolic extracts from Millingtonia hortensis L.f. and Oroxylum indicum (L.) Kurz (Bignoniaceae). Issue 4 (16th February 2023) - Cardoso Reis, Adriana Cotta; Valente, Gabriel Mendonça; Silva, Breno de Mello; de Brito Magalhães, Cíntia Lopes; Kohlhoff, Markus; Brandão, Geraldo Célio
Abstract: Millingtonia hortensis L.f. and Oroxylum indicum (L.) Kurz (Bignoniaceae) are native species from the Asian continent. They are popularly used in traditional medicine and their extracts are rich in flavonoids. In this work, ethanolic extracts of stems and leaves of these species were evaluated against the Chikungunya, Zika and Mayaro virus. The extracts were subjected to analysis by ultra-efficient liquid chromatography coupled to mass spectrometry. Additionally, M. hortensis leaves extract was fractionated, leading to the isolation of hispidulin. Anti-arboviral activity against the three viruses was detected for M. hortensis leaves extract with EC50 ranging from 37.8 to 134.1 µg/mL and for O. indicum stems extract with EC50 ranging from 18.6 to 55.9 µg/mL. Hispidulin inhibited viral cytopathic effect of MAYV (EC50 value 32.2 µM) and CHIKV (EC50 value 78.8 µM). In LC-DAD-ESI-MS/MS analysis we characterized 25 flavonoids confirming once again the presence of these substances in extracts of these species. Graphical Abstract: UF0001